Autonomy and identity: the role of two developmental tasks on adolescent's wellbeing - Ruiz, Wawie D. G.; Yabut, Homer J. (Frontiers in Psychology, 2024)
Developmental tasks theory suggests that the wellbeing of adolescents can be better understood by considering their developmental tasks, rather than just viewing it as a specific age. This concept has significantly influenced contemporary studies on the transition to adulthood. Study explains that psychosocial developmental tasks involve shifts in an individual's psychological state and social relationships, potentially disrupting their previous equilibrium. Authors stress the importance of forming personal identity and fostering a healthy sense of independence, especially concerning identity and autonomy tasks, as crucial elements for adolescent wellbeing analysis. In line with this, the study focuses on the concurrent and predictive relationship between identity process of commitment, emotional autonomy, and psychological wellbeing among adolescents. Four hundred fifty-four (454) participants with an age ranged from 15 to 19 years (m = 17.96) completed surveys measuring emotional autonomy, identity commitment, and psychological wellbeing. The findings revealed that both emotional autonomy and identity commitment predicted psychological wellbeing, but in different ways. The study revealed that emotional autonomy is inversely associated with psychological wellbeing in middle and late adolescents, indicating that their ability to establish independence from their parents or relinquish unrealistic parental expectations may be linked to a decline in their mental health. The results also indicated that identity commitment is moderately and positively related to psychological wellbeing, suggesting that when adolescents have a clear sense of their identity, they may experience greater wellbeing. This finding underscores the importance of encouraging adolescents to explore their values, interests, and goals, as well as providing them with support and guidance throughout the process. Additionally, the findings of the study revealed that emotional autonomy has a negative influence on psychological wellbeing when identity commitment is low or average. Specifically, when individuals have a low level of identity commitment, emotional autonomy significantly predicts lower psychological wellbeing. Similarly, when identity commitment is at an average level, emotional autonomy also has a detrimental effect on psychological wellbeing. Lastly, the study revealed that when individuals have a high level of identity commitment, emotional autonomy does not have a significant impact on psychological wellbeing. In simpler terms, when individuals possess a strong sense of commitment to their identity, their level of emotional autonomy does not play a significant role in influencing their psychological wellbeing.